Metodologia de projeto de instalações elétricas: estudo de caso na Escola Municipal Francisco Torquato Rêgo - Silva, Herik Roberto Rodrigues (Universidade Federal Rural do Semi-Árido, 2017)
The importance of electricity in our lives is unquestionable. In homes, shops, industries, hospitals and schools the electrical installation is present, on the other hand, when misused, poses some dangers to the health and safety of individuals, becoming one of the main responsible for accidents in Brazil and the world. In the institution, object of analysis, it is necessary to pay attention to the possible risks that people and the institution are exposed, whether they are risks that cause damage in the short or long term and / or risk of life. As an example, there is a risk of electric shock to people and economic damages to the institution (fire and explosion). Therefore, it is extremely important to carry out a study in the workplace, identifying possible situations of risk to the citizens in order to institute methodologies that can solve the problem. In fact, this work has as general objective to apply methodologies or the design of electrical installations in educational spaces, taking as reference the Municipal School Francisco Torquato do Rêgo located in the city of Pau dos Ferros, Rio Grande do Norte, understanding the existing problem and showing Solvable techniques.
Keywords: Eletricidade; Projeto; Projeto Elétrico; Escola; Pau dos Ferros-RN; Electricity; Project; Electrical project; School; Pau dos Ferros-RN; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA